Dust charging processes with a Cairns-Tsallis distribution function with negative ions - Abid, A.A.; Khan, M.Z.; Yap, S.L.; Terças, H.; Mahmood, S. (American Institute of Physics, 2016)
Dust grain charging processes are presented in a non-Maxwellian dusty plasma following the Cairns-Tsallis (q, α)-distribution, whose constituents are the electrons, as well as the positive/negative ions and negatively charged dust grains. For this purpose, we have solved the current balance equation for a negatively charged dust grain to achieve an equilibrium state value (viz., qd = constant) in the presence of Cairns-Tsallis (q, α)-distribution. In fact, the current balance equation becomes modified due to the Boltzmannian/streaming distributed negative ions. It is numerically found that the relevant plasma parameters, such as the spectral indexes q and α, the positive ion-to-electron temperature ratio, and the negative ion streaming speed (U0) significantly affect the dust grain surface potential. It is also shown that in the limit q → 1 the Cairns-Tsallis reduces to the Cairns distribution; for α = 0 the Cairns-Tsallis distribution reduces to pure Tsallis distribution and the latter reduces to Maxwellian distribution for q → 1 and α = 0.